Inovasi Pembuatan Sistem Inspeksi Alat Pemadam Api Ringan Berbasis Website Di PT. Semen Indonesia Logistik - Dewi, Fitri Rahma; Sahri, Moch.; Ayu, Friska; Rhomadhoni, Muslikha Nourma (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
Inspection of Light Fire Extinguishers is one of the important steps in maintaining safety in the work environment. PT. Semen Indonesia Logistik previously conducted inspection of Light Fire Extinguishers manually, which caused problems such as delays in recording, lack of data accuracy, and difficulty in monitoring inspection history. This study aims to describe the manual inspection of Light Fire Extinguishers process, implement a website-based inspection system, and evaluate the effectiveness of the system in improving inspection accuracy and efficiency. The research method used is development research with the stages of needs analysis, system design, implementation, and evaluation. The system is developed using the Laravel framework and applies QR Code technology to facilitate the identification of Light Fire Extinguisher. Based on the conclusions from the analysis and discussion, the website-based APAR inspection system developed has proven effective in supporting inspection activities at PT. Semen Indonesia Logistik. The implementation of this technology not only improves work efficiency but also strengthens transparency and accountability in the management of Light Fire Extinguisher.